UPAYA MENJAGA KONDISI SEKOLAH YANG SEHAT UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS III: TINJAUAN TERHADAP KESIAPAN SEKOLAH DALAM MENCIPTAKAN BUDAYA SEKOLAH SEHAT - Andreas Yoga Sabatyasno; Henry Aditia Rigianti (STKIP Subang, 2023)
Healthy school conditions play an important role in increasing student interest in learning. This research focuses on efforts that can be made by schools in maintaining healthy conditions, especially for third grade students. Based on the literature study, it was found that healthy schools have certain characteristics such as a clean learning environment, good air circulation, and adequate hand washing and sanitation facilities. School readiness in creating a healthy school culture can be seen from the active role of the school in educating students about the importance of health, involving parents of students in school health programs, and the involvement of school committees in monitoring and evaluation. In addition, the provision of facilities and hygiene principles is also important to be applied in order to maintain the health of students. Thus, efforts to maintain healthy school conditions can improve the quality of education and increase students' interest in learning in class III.